Effect of fungicides on in vitro pollen germinationand tube growth in Brassica juncea - NARESH MEHTA*; M.S. SANGWAN, ANJALI JAIN, H.R. DHINGRA (Indian Phytopathology, 2002)
The effects of Dithane M-45 [mancozeb] and Ridomil MZ-72 (metalaxyl) on the pollen functions of two susceptible cultivars of Brassica juncea (RH-30 and RH-8812) were studied at Hisar during rabi 1996. Freshly released pollen was collected and mixedwith the fungicides (0.025, 0.05, 0.1, 0.15 and 0.2% concentrations) in Petri dishes and incubated at 25?â„ƒ for 24 h. Dithane M-45 inhibited both pollen germination and tube growth. Inhibition of germination was more in RH-8812 than in RH-30, although germination was completely inhibited in RH-30 with the 0.2% concentration. Lower concentration (0.025%) of Dithane M-45 decreased tube length significantly (38.84%) in RH-30 but did not affect tube growth in RH-8812. Pollen germination decreased with increasing concentration of Ridomil MZ-72 and was completely inhibited at a concentratin of 0.15% and above. The overall reduction in germination was more severe in RH-8812 than in RH-30, but the converse was true for tube growth.